KIT coaxial gyrotron development: from ITER toward DEMO. Issue 5 (5th July 2018) - Ruess, S.; Avramidis, K. A.; Fuchs, M.; Gantenbein, G.; Ioannidis, Z.; Illy, S.; Jin, J.; Kalaria, P. C.; Kobarg, T.; Pagonakis, I. Gr.; Ruess, T.; Rzesnicki, T.; et al.
Abstract : Karlsruhe Institute of Technology (KIT) is doing research and development in the field of megawatt-class radio frequency (RF) sources (gyrotrons) for the Electron Cyclotron Resonance Heating (ECRH) systems of the International Thermonuclear Experimental Reactor (ITER) and the DEMOnstration Fusion Power Plant that will follow ITER. In the focus is the development and verification of the European coaxial-cavity gyrotron technology which shall lead to gyrotrons operating at an RF output power significantly larger than 1 MW CW and at an operating frequency above 200 GHz. A major step into that direction is the final verification of the European 170 GHz 2 MW coaxial-cavity pre-prototype at longer pulses up to 1 s. It bases on the upgrade of an already existing highly modular short-pulse (ms-range) pre-prototype. That pre-prototype has shown a world record output power of 2.2 MW already. This paper summarizes briefly the already achieved experimental results using the short-pulse pre-prototype and discusses in detail the design and manufacturing process of the upgrade of the pre-prototype toward longer pulses up to 1 s.